SPACE INSURANCE FOR SMALL SATELLITE LAUNCH AND OPERATION IN THE SETTING OF INDONESIAN LAW - Pratama, Garry Gumelar; Ruswandi, Nadhifathur Rochmah (Department of Transnational Business Law, Faculty of Law Universitas Padjadjaran, 2021)
The topic of liability under international law falls in the norms of the Outer Space Treaty 1967 and the Liability Convention 1972. The principled division of responsibility for harm incurred by a space object to the launching state(s) is the starting point in this regard. Since the conventions are legally binding for Indonesia, it become the outlining frame for regulating space insurance with national regulations. As small satellite industry and space insurance in Indonesia show a massive potential grow, this article focuses on the analytical explanation of Indonesian space insurance-related regulations covering small satellite operations. Even though international law does not require obligatory space insurance, Indonesian Space Act 2013 regulates mandatory requirement for all space activities conducted by private companies, including small satellites. One of the main issues discussed in this paper is whether the Indonesia regulation open opportunities to space insurance industry in Indonesia to grow. The study was conducted using descriptive-analytical approach, emphasizing on the normative juridical approach by literature studies.